A Tale of Two Additives: Effects of Glutaric and Citraconic Anhydrides on Lithium-Ion Cell Performance. Issue 4 (1st January 2019) - Hall, David S.; Li, Jing; Lin, Katherine; Stakheiko, Nikolai; Baltazar, Jazmin; Dahn, J. R.
Abstract : The use of electrolyte additives is an important method to improve lithium-ion cell lifetime and performance without significantly affecting costs. This work evaluates two organic anhydrides, glutaric anhydride (GA) and citraconic anhydride (CA), as additives in Li(Ni0.6 Mn0.2 Co0.2 )O2 (NMC622)/graphite and Li(Ni0.5 Mn0.3 Co0.2 )O2 (NMC532)/graphite pouch cells, using ultrahigh precision coulometry and high-temperature storage. The additives were tested singly and in binary blends. GA-based additive blends give high coulombic efficiencies (CEs) and good storage performance. However, GA leads to substantial impedance during formation. Most notably, GA is extremely effective at suppressing gas during cell formation and storage. Whereas CA-containing blends yield good CEs, they show rapid voltage drop during storage. Both additives may provide specific benefits for target applications. Long-term cycling data indicates that GA is a negative electrode SEI-forming additive that is useful for capacity retention and limiting cell impedance growth when used as a binary blend with vinylene carbonate or lithium difluorophosphate. These results are also intended to facilitate comparison between chemically related additives in order to better understand the underlying chemistry behind their function in lithium-ion cells.